15-16 yaşları arasındaki çalışan,Resmi Lise ve Endüstri Meslek Lisesine devam eden gençlerin özsaygı düzeyleri ve denetim odaklarının karşılaştırılması - Erol, Zehra (My University, 2000)
15-16 YAŞLARI ARASINDAKİ ÇALIŞAN, RESMİ LİSE VE ENDÜSTRİ MESLEK LİSESİNE DEVAM EDEN GENÇLERİN ÖZSAYGI DÜZEYLERİ VE DENETİM ODAKLARININ KARŞILAŞTIRILMASI. Araştırmanın amacı; çalışan, resmi lise (RL) ve endüstri meslek liselerinde (EML) okuyan 15-16 yaşları arasındaki gençlerin özsaygı düzeyleri ve denetim odaklarının karşılaştırılmasıdır. Araştırmanın evrenini, İstanbul'un Kartal ve Ümraniye ilçelerindeki Kartal Lisesi, Ümraniye Atakent Lisesi , Kartal ve Ümraniye Endüstri Meslek Lisesi öğrencileri ile bu ilçelerde çıraklık eğitimi almadan, çalışan gençler oluşturmaktadır. Örneklem random olarak seçilen 941 gençten oluşmuştur. Örneklemin özsaygı düzeylerini ve denetim odaklarını belirlemek için Rosenberg Benlik Saygısı Ölçeği, Nowıckı Strıckland Denetim Odağı Ölçeği ve demografik bilgilerini saptamak için hazırlanan Kişisel Bilgi Formları uygulanmıştır. Araştırma grubunun; cinsiyet, anne-babanın birlikte olma durumuna, anne-babanın birlikte olmama nedenine, aylık gelirlerini yeterli bulmalarına, sigara ve alkol kullanmalarına, çalışma nedenlerine, RL ve EML'ne devam eden gençlerin; okul başarı durumunu değerlendirmelerine çalışan gençlerin; okulu terk ettikleri sınıf düzeyine, meslekte ilerlemeyi düşünme durumlarına göre özsaygı düzeylerinin ve denetim odaklarının karşılaştırılması için iki boyutlu varyans analizi ve t testi (iki boyutlu varyans analizine göre manidar çıkan sonuçlara) uygulanmıştır. RL ve EML'ne devam eden gençlerin; özsaygı düzeyleri ve denetim odaklarının; sınıf düzeyine, okuldan artakalan vakitlerinde ve yaz tatillerinde işte çalışma durumlarına göre karşılaştırılması için bağımsız grup t testi uygulanmıştır. Araştırma grubunun sosyal faaliyetlere katılma durumu, televizyon izleme süreleri, RL ve EML'ne devam eden gençlerin ders çalışma süreleri ile denetim odakları ve özsaygı düzeyleri arasındaki ilişkiyi bulmak için pearson çarpım moment katsayısı hesaplanmıştır. Özsaygı alttestlerinden ve denetim odağı ölçeğinden elde edilen bulgular; EML öğrencilerinin özsaygı düzeylerinin çalışan ve RL devam edenlere göre daha yüksek olduğunu; çalışan ve RL devam edenlere göre daha içten denetimli oldukları sonucunu ortaya koymaktadır. COMPARISONS OF THE LOCUS OF CONTROL AND THE LEVEL OF SELF ESTEEM OF THE REGULAR HIGHSCHOOL AND VOCATIONAL SCHOOL WORKING ATTENDEES BETWEEN 15-16 YEARS. Purpose of the research was to compare the self esteem levels and the locus of control of the children between the ages of 15-16 years of working and attending regular and vocational highschools. Coverage of the research containing the students without taking training but working and attending the Kartal Lycee', Ümraniye Atakent Lycee', Kartal and Ümraniye Vocational Highschools of Kartal and Ümraniye counties of İstanbul. Sample pattern consisted of randomly selected 941 students. In order to determine the level of the self-esteem and the locus of control of the sample pattern Rosenberg Self-Esteem Scale, Nowıckı Strıckland's Locus of Control Scale and determine the the demographic informations Personal Information Forms have been used. In order to compare the locus of control and self-esteem levels two dimensional varians analysis and t test have been applied. The investigational group; established variances of the different sexes, parents of being together, the reasons of parents being not together, believing of having enough mounthly income, cigarette and alchol use, reason to work, the regular high school and vocational school attendies their successes at their school or drop out levels and their desire to achieve in theire professions. In order to make comparisons between the levels of the self-esteem and locus of control of the attendies of the regular highschool and vocational schools, grade levels and depending on the part-time and summer-time working situations, independent t test have been applied. In order to find out the relationship between the amount of time to study and the locus of control and the level of self-esteem of the investigated group pearson multiplication momentum coefficient has been calculated, based upon the participation into the social activities, durations of watching television of the regular highscool and the vocational school attendies. The findings of the self-esteem subtest and the locus of control have been revealed that self-esteem levels of the workıng vocational school students are higher than the regular highschool attendies and that they have internal locus of control than the workıng , regular hıghschool students. COMPARISONS OF THE LOCUS OF CONTROL AND THE LEVEL OF SELF ESTEEM OF THE REGULAR HIGHSCOOL AND VOCATIONAL SCHOOL WORKING ATTENDEES. Purpose of the research was to compare the self esteem levels and the locus of control of the children between the ages of 15-16 years of working and attending regular and vocational highschools. Coverage of the research containing the students without taking training but working and attending the Kartal Lycee', Ümraniye Atakent Lycee', Kartal and Ümraniye Vocational Highschools of Kartal and Ümraniye counties of İstanbul. Sample pattern consisted of randomly selected 941 students. In order to determine the level of the self-esteem and the locus of control of the sample pattern Rosenberg Self-Esteem Scale, Nowıckı Strıckland's Locus of Control Scale and determine the the demographic informations Personal Information Forms have been used. In order to compare the locus of control and self-esteem levels two dimensional varians analysis and t test have been applied. The investigational group; established variances of the different sexes, parents of being together, the reasons of parents being not together, believing of having enough mounthly income, cigarette and alchol use, reason to work, the regular high school and vocational school attendies their successes at their school or drop out levels and their desire to achieve in theire professions. In order to make comparisons between the levels of the self-esteem and locus of control of the attendies of the regular highschool and vocational schools, grade levels and depending on the part-time and summer-time working situations, independent t test have been applied. In order to find out the relationship between the amount of time to study and the locus of control and the level of self-esteem of the investigated group pearson multiplication momentum coefficient has been calculated, based upon the participation into the social activities, durations of watching television of the regular highscool and the vocational school attendies. The findings of the self-esteem subtest and the locus of control have been revealed that self-esteem levels of the workıng vocational school students are higher than the regular highschool attendies and that they have internal locus of control than the workıng , regular hıghschool students.
Keywords: EĞİTİM,GENÇLİK; PSİKOLOJİK HİZMETLER